Understanding the Meaning of Maqashid Syariah in Designing Financial Statement Objectives - Wijandari, Ana (Fin Sinergy: Jurnal Manajemen Keuangan, 2023)
This article focuses on the importance of understanding and integrating Maqashid Syariah principles in designing financial report objectives. The objectives of traditional financial reports tend to be limited to financial aspects alone, ignoring ethical, moral and social benefit dimensions. However, in an economic environment based on Islamic values, the need to direct financial reports towards achieving the public benefit becomes increasingly important. By applying a conceptual analysis approach and literature review, this article explores the concept of Maqashid Syariah and how its principles can be integrated into the objectives of financial reporting . The results of the analysis show that understanding the meaning of Maqashid Syariah brings a paradigm shift in formulating the objectives of financial reports. Apart from emphasizing transparency and accountability, more inclusive goals such as social justice, community benefit, and the fulfillment of individual rights are more emphasized aspects. This article provides a more in-depth view of how the concept of Maqashid Syariah can provide direction in overcoming contemporary economic challenges and bridging the gap between the financial and ethical dimensions of financial reporting. By embracing Maqashid Syariah principles in designing financial reporting objectives, companies can contribute to the realization of an economy that is fairer, more sustainable and in accordance with Islamic principles.